Drawing on the continuum: a war and post-war political economy of gender-based violence in Bosnia and Herzegovina - Bojicic-Dzelilovic, Vesna (2020)
Current understandings of why and how gender-based violence continues beyond the end of conflict remain siloed along theoretical and disciplinary lines. Recent scholarship has addressed the neglected structural dimension when examining the incidence and variation of post-conflict gender-based violence. In particular, continuum of violence and feminist political economy perspectives have offered accounts of gender-based violence during and after conflict. However, these approaches overlook how war and post-war economic processes interact over time and co-constitute the material basis for the continuation of gender-based violence. The war and post-war political economy perspective that we leverage examines critically the distinction, both in theory and practice, between global and local dynamics, and between formal and informal actors in post-conflict societies. Exposing these neglected structural and historical interconnections with evidence from post-conflict Bosnia and Herzegovina, we demonstrate that the material basis of gender-based violence is a cumulative result of political and socio-economic dynamics along the war-to-peace trajectory. Our findings point to the need to be attentive to the enduring material consequences of interests and incentives formed through war, and to the impact of post-war global governance ideologies that transform local conditions conducive to gender-based violence